ENGLISH MATERIAL ADAPTATION IN LAN (LEMBAGA ADMINISTRASI NEGARA)LANGUAGE CENTRE - Risma Anggoro, - (2008)
This research is entitled "English Materials Adaptation in LAN (Lembaga Administrasi Negara) Language Centre". The aim of this research is to investigate how LAN Language Centre English instructors adapt their English materials. The sample of the research is four LAN Language Centre instructors. The research was conducted in descriptive method. Interview and document analysis were the instruments to collect the data. The findings of the research show that LAN Language Centre instructors' strategy in adapting material is by replacing, adding, modifying, and re-ordering the materials This research indicated that first, well trained instructors may provide the appropriate materials to help students enjoying the learning activities and the materials delivered. Second, employing different procedures in different condition may provide suitable supplementary materials to the main resource. Third, Students' characteristics can play important role to take into consideration when instructors prepare their materials. Forth, enjoyable teaching-learning activities seem to be perceived as important consideration when they are preparing materials. Fifth, Additional resources available can bring instructors advantages in providing students suitable materials.